2022
DOI: 10.1016/j.jinf.2021.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 by children and young people in households and schools: A meta-analysis of population-based and contact-tracing studies

Abstract: Background The role of children and young people (CYP) in transmission of SARS-CoV-2 in household and educational settings remains unclear. We undertook a systematic review and meta-analysis of contact-tracing and population-based studies at low risk of bias. Methods We searched 4 electronic databases on 28 July 2021 for contact-tracing studies and population-based studies informative about transmission of SARS-CoV-2 from 0-19 year olds in household or educational settings. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 73 publications
4
35
0
2
Order By: Relevance
“…A recent systematic review and meta-analysis showed that children transmit the virus to other children at lower rates than to adults [ 17 ]. Another study found that there was no difference in the transmission of SARS-CoV-2 in children compared with adults in households [ 18 ]. Based on recent data, the average number of births per woman in Israel is 3.0, while it is about half of that in many European countries and the US [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis showed that children transmit the virus to other children at lower rates than to adults [ 17 ]. Another study found that there was no difference in the transmission of SARS-CoV-2 in children compared with adults in households [ 18 ]. Based on recent data, the average number of births per woman in Israel is 3.0, while it is about half of that in many European countries and the US [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al igual que series internacionales, la incidencia en nuestro país de COVID-19 en NNA ha sido muy dependiente de la circulación comunitaria del virus, y no así de medidas específicas para limitar su exposición 11,12 . Esto apoya a las observaciones que refieren que los niños en su mayoría se exponen al virus en su domicilio, y su rol en la transmisión y circulación viral a nivel poblacional es baja, a diferencia de otros virus, como la influenza [13][14][15][16] .…”
Section: ¿Qué Aporta Este Estudio a Lo Ya Conocido?unclassified
“…Recently published studies 35 , 36 , 37 have reported that reopening schools, as long as appropriate hygiene and social distancing measures were upheld, did not seem to have a deleterious impact, although most studies acknowledged that the behaviour of new variants of the virus could change this. At the same time, numerous studies highlighted the negative impact of school closures on different aspects of child and adolescent health.…”
Section: Updates On Preventionmentioning
confidence: 99%